Rubber intercropping with arboreal and herbaceous species alleviated the global warming potential through the reduction of soil greenhouse gas emissions - Tahir Ashar; Yingying Zhang; Chuan Yang; Wenxian Xu; Muhammad Zeeshan Ul Haq; Hassam Tahir; Hafiz Muhammad Mazhar Abbas; Zhixiang Wu (Scientific Reports)
Abstract Agroforestry systems are known to enhance soil health and climate resilience, but their impact on greenhouse gas (GHG) emissions in rubber-based agroforestry systems across diverse configurations is not fully understood. Here, six representative rubber-based agroforestry systems (encompassing rubber trees intercropped with arboreal, shrub, and herbaceous species) were selected based on a preliminary investigation, including Hevea brasiliensis intercropping with Alpinia oxyphylla (AOM), Alpinia katsumadai (AKH), Coffea arabica (CAA), Theobroma cacao (TCA), Cinnamomum cassia (CCA), and Pandanus amaryllifolius (PAR), and a rubber monoculture as control (RM). Soil physicochemical properties, enzyme activities, and GHG emission characteristics were determined at 0–20 cm soil depth. The results showed that agroforestry systems significantly enhanced most of soil nutrient levels and enzyme activities. In 0–20 cm soil depth, all rubber plantations acted as net carbon dioxide (CO₂) and nitrous oxide (N₂O) resources, and net methane (CH₄) sinks. Compared with the RM, the CAA and CCA systems significantly increased the cumulative CO2 and N2O emissions, and the global warming potential (GWP) significantly increased in the CAA (36.78%) and CCA (7.18%) systems, whereas it significantly decreased in the AOM (6.61%), AKH (24.96%), TCA (14.24%), and PAR (41.01%) systems. The soil DOC concentration was the primary factor influencing GHG emissions and GWP. This study provides novel insights into GHG emissions from rubber agroforestry systems and serves as a fundamental reference for climate-smart land use management in rubber plantations. Intercropping rubber trees with arboreal and herbaceous species is recommended over shrub species, considering their beneficial effects in reducing soil GHG emissions and GWP for the sustainable development of rubber plantations on Hainan Island.